Reformulasi Mekanisme Perlindungan Kesehatan Mental Pekerja dalam Peraturan Perusahaan Berdasarkan Pedoman WHO (RechtJiva, 2024)
Crime rates and various forms of crime indicate that society is experiencing an identity, moral and spiritual crisis. Mental health is becoming a pressing issue that affects the productivity, economy and well-being of society at large. Untreated mental disorders, such as depression, cause negative impacts on individuals, families, and countries, with huge economic and social costs. Although there are labour regulations in Indonesia that protect occupational health, the mental health aspects of workers have not been specifically regulated. This research aims to analyse the protection of workers' mental health in positive law in Indonesia and the United States, and to analyse and design the concept of regulating workers' mental health protection mechanisms in company regulations in Indonesia.. This journal research uses a normative juridical research method by taking a statutory, comparative and conceptual approach. Primary, secondary and tertiary legal materials obtained by the author will be analysed using literature study search techniques and analysis techniques in the form of grammatical interpretation and comparative interpretation. A comparison between Indonesia and the United States in protecting workers' mental health shows that the United States is more progressive with guidelines and laws that meet international standards, such as the WHO Guidelines of Mental Health at Work. Meanwhile, Indonesia still has repressive and less specific regulations. Reformulation of the law in Indonesia is needed to create more comprehensive mental health protection for workers, in line with the development of international standards such as in the United States.